In-situ carbon-coated sodium ferrous sulfate composite positive electrode material, preparation and sodium ion battery
The porous sodium ferrous sulfate composite cathode material prepared through evaporative crystallization and in-situ carbon coating technology solves the problems of low conductivity and moisture sensitivity of existing materials and achieves efficient sodium-ion battery performance.
Patent Information
- Application Number
- CN202310358536.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-04-06
AI Technical Summary
The existing cathode material of sodium ion battery, sodium ferrous sulfate, has limited its application in sodium ion batteries due to its low conductivity, slow kinetics, poor rate performance and moisture sensitivity.
Using a technology that combines evaporative crystallization and in-situ carbon coating, a high-purity precursor is obtained through natural crystallization in one step through rapid evaporation of water at 60-100°C in a vacuum, followed by pre-calcination at 200-250°C and calcination at 410-430°C. Thermal reduction forms a porous sodium ferrous sulfate composite cathode material with an amorphous carbon coating.
It improves the electronic and ionic conductivity of the material, excellent rate performance and cycle performance, while enhancing the resistance to moisture and oxygen and improving environmental tolerance.
Smart Images

Figure CN116354405B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material, preparation method and a sodium ion battery, belonging to the technical field of sodium ion batteries. Background Art
[0002] The development of large-scale energy storage systems is crucial for the application of intermittent renewable energy sources such as solar energy, wind energy, and tidal energy. Lithium-ion batteries with LiFePO4 (LFP) positive electrodes have been explored in wind and solar integrated energy storage systems due to their advantages such as long cycle life, high safety, and low cost. Considering the scarcity and regional distribution of lithium reserves, existing lithium-ion batteries are bound to be unable to simultaneously meet the explosive application of future electric vehicles and smart grid-scale energy storage. Sodium-ion batteries, which are rich in crustal elements, environmentally friendly, and safe, seem to be a better alternative for the upcoming grid-scale energy storage, but existing sodium-ion battery technology cannot meet the requirements of practical applications. Therefore, the development of sodium-ion batteries with low cost, safety, environmental friendliness, and long cycle life has become an urgent need.
[0003] In the sodium ion battery system, the cathode material determines the energy density and cycle life of the battery to a large extent. Compared with transition metal oxides and Prussian blue analogs, polyanion oxide cathodes have high thermal stability, ultra-long cycle life and adjustable voltage. In particular, the Alluaudite type sodium ferrous sulfate cathode material has the highest Fe 2+ / Fe 3+ Redox potential (~3.8V). Compared with other polyanion cathode materials, the higher working voltage of this material can make up for the disadvantage of lower specific capacity caused by the larger mass of the polyanion group, and can also provide satisfactory energy density. However, the sodium ferrous sulfate cathode material has low conductivity, resulting in slow kinetics and poor rate performance; at the same time, it is sensitive to moisture and easily decomposes to produce SO above 450°C. x Gas, which limits the sodium ferrous sulfate positive electrode material and is still unable to fully replicate the success of lithium iron phosphate (LFP).
[0004] Existing preparation methods include the combination of high-energy mechanical ball milling technology and low-temperature solid-state sintering technology, co-precipitation combined with low-temperature solid-phase sintering technology, etc. to prepare sodium ferrous sulfate materials.
[0005] The method combining high-energy mechanical ball milling technology and low-temperature solid-state sintering must first prepare anhydrous FeSO4 by vacuum drying FeSO4·7H2O for 2 to 4 hours, then high-energy ball milling Na2SO4 and anhydrous FeSO4 for 4 to 8 hours under an inert atmosphere (mostly argon or nitrogen), and then sintering at 350-400°C for 12 to 24 hours. This scheme has complicated steps for preparing precursors and consumes a lot of energy, and has strict requirements on the production environment and equipment. At the same time, the combination of active material particles and carbon sources obtained by ball milling is mostly point contact, which makes it difficult to build a highly conductive network.
[0006] Co-precipitation technology and low-temperature solid-phase sintering technology use the characteristics of the precursor Na2Fe(SO4)·4H2O being insoluble in hydrophobic alcohol, and use a large amount of anhydrous ethanol and other hydrophobic alcohols as precipitation solutions. Usually, 500 to 2000 mL of ethanol is required for every 50 to 100 mL of reaction solution to make the precipitation complete. During the experiment, the reaction solution needs to be added dropwise to the hydrophobic alcohol. The precipitation reaction time is long, and then the mixed suspension needs to be slowly vacuum filtered for 1 to 2 hours, vacuum dried for more than 6 hours to obtain the precursor, and then calcined at 300 to 400°C for 8 to 48 hours to obtain the product. The recycling and purification of a large amount of high-purity anhydrous ethanol during the experiment makes this method difficult to apply on a large scale. Summary of the invention
[0007] In view of this, the object of the present invention is to provide an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material, preparation and sodium ion battery. The technology of combining evaporation crystallization and in-situ carbon coating is adopted, the operation steps are simple, the experimental conditions are low, and Na2SO4, FeSO4·7H2O and water-soluble carbon source are directly used as reactants. The water is quickly evaporated at 60-100°C in a vacuum and naturally crystallized to obtain a high-purity precursor in one step. The precursor is first pre-calcined at 200-250°C for 1-2h, and then calcined at 410-430°C for 8-12h. Carbon thermal reduction is performed to obtain a porous sodium ferrous sulfate composite positive electrode material with a uniform amorphous carbon layer on the surface. The amorphous carbon layer can inhibit the excessive growth of particles during the sintering process, and at the same time, it can prevent the electrolyte from further eroding the active material during the cyclic charge and discharge process. The porous structure is conducive to the penetration of the electrolyte and the increase of the active sites for the sodium ion reaction, greatly improving the electronic and ionic conductivity of the material, thereby showing excellent rate performance and cycle performance.
[0008] To achieve the above object, the technical solution of the present invention is as follows:
[0009] An in-situ carbon-coated sodium ferrous sulfate composite positive electrode material, the composite positive electrode material is a porous structure, the secondary particle size is 5 to 10 μm, and the primary particles of 50 to 80 nm are closely stacked; amorphous carbon is coated on the surface of the primary particles, and the total mass of the amorphous carbon is 5 to 15 wt% of the total mass of the sodium ferrous sulfate composite positive electrode material.
[0010] The method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material of the present invention comprises the following steps:
[0011] (1) Preparing precursor powder by vacuum evaporation crystallization: Na2SO4, FeSO4·7H2O, and a water-soluble carbon source are added to deionized water, and stirred thoroughly to obtain a uniform light green solution. The solution is then rapidly evaporated at 60-100°C under vacuum to obtain a precursor powder;
[0012] (2) Preparation of composite positive electrode materials by a two-stage solid-phase calcination method: The precursor powder is ground evenly and placed in a tubular furnace with a protective gas atmosphere. The temperature is first raised to 200°C to 250°C for pre-calcination for 1 to 2 hours, and then the temperature is raised to 410 to 430°C for calcination for 8 to 12 hours. After the calcination, an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material is obtained.
[0013] Preferably, in step (1), the molar ratio of Na2SO4 to FeSO4·7H2O is 1:1-2.
[0014] Preferably, in step (1), the water-soluble carbon source is one or more of ascorbic acid, citric acid, hydroxymethyl cellulose and cyclodextrin.
[0015] Preferably, in step (1), the molar ratio of the water-soluble carbon source to FeSO4·7H2O is 1:10-100.
[0016] Preferably, in step (2), the protective gas is an inert gas (a gaseous substance corresponding to the Group 0 element in the periodic table) or a mixed gas of an inert gas and hydrogen, and the volume fraction of hydrogen in the mixed gas is 5% to 10%.
[0017] Preferably, in step (2), the heating rates during pre-calcination and calcination are 1-5° C. / min, respectively.
[0018] A sodium ion battery is composed of a current collector, a positive electrode sheet, a negative electrode sheet, an electrolyte, a diaphragm and a battery shell, characterized in that: the current collector is aluminum foil, the in-situ carbon-coated sodium ferrous sulfate composite positive electrode material described in the present invention is the positive electrode, metallic sodium is the negative electrode, the glass fiber filter membrane is the diaphragm, and the electrolyte is a soluble sodium salt organic solution.
[0019] Preferably, the positive electrode sheet of the sodium ion battery is obtained by coating a slurry obtained by uniformly mixing a positive electrode, a conductive agent, a binder and a dispersant onto an aluminum foil current collector; the negative electrode sheet of the sodium ion battery is obtained by mechanically pressing metallic sodium and aluminum foil; and the battery shell adopts a CR2032 battery shell.
[0020] Preferably, the conductive agent is one or more of acetylene black, Ketjen black and Super P; the binder is polyvinylidene chloride (PVDF); the dispersant is 1-methyl-2-pyrrolidone (NMP); the soluble sodium salt in the electrolyte is sodium hexafluorophosphate (NaPF6) or sodium perchlorate (NaClO4); the organic solvent in the electrolyte is one or more of ethylene carbonate (EC), vinylene carbonate (DEC), propylene carbonate (PC), dimethyl carbonate (DMC) and fluoroethylene carbonate (FEC); the battery shell material is organic plastic, aluminum shell, aluminum-plastic film, stainless steel or their composite materials.
[0021] Beneficial Effects
[0022] The present invention provides an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material, the composite positive electrode material includes an in-situ carbon coating layer and a sodium ferrous sulfate active ingredient, in which the amorphous carbon coating layer is tightly combined with the sodium ferrous sulfate particles to form uniform porous micron particles, providing a sufficient conductive network for electron transfer, greatly improving the rate performance of the material; in addition, the uniform coating of the carbon coating layer improves the material's resistance to moisture and oxygen, and improves the material's environmental tolerance. The composite material has a unique porous structure, which is conducive to the penetration of the electrolyte and the increase of sodium ion reaction active sites, thereby stably improving the conductivity, cycle stability, environmental stability and other physical and chemical properties of the sodium ferrous sulfate composite positive electrode material.
[0023] The invention provides a method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material. The secondary particle size of the positive electrode material prepared by evaporation crystallization and solid phase calcination is about 5-10 μm, and the material is formed by closely stacking primary particles of 50-80 nm in size. The added organic carbon sources are all water-soluble, and are evenly distributed in the precursor particles during the evaporation crystallization process. In the subsequent solid phase sintering process, carbon thermal reduction forms a continuous amorphous carbon coating layer, which effectively inhibits further abnormal growth of sodium ferrous sulfate crystal particles. At the same time, the volatilization of gas and water generated by pyrolysis of the organic carbon source helps to build a porous structure on the surface of the micron particles, which helps the penetration of the electrolyte and provides abundant sodium ion reaction active sites for the charging and discharging process.
[0024] The invention provides a method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material, wherein rapid vacuum evaporation and dehydration at 60-100° C. are performed during the preparation of a precursor, thereby ensuring that a high-purity precursor is obtained in a short time. The evaporation temperature needs to be strictly controlled during the process. When the evaporation temperature is 110-130° C., the precursor Na2Fe(SO4)2·4H2O will be converted into Na2Fe(SO4)2·2H2O impurities. When the evaporation temperature is above 130° C., the precursor Na2Fe(SO4)2·4H2O will be decomposed into impurities such as Na2Fe(SO4)2·H2O, Fe(SO4)·H2O and NaSO4. During the solid-phase calcination method, pre-calcination at 200-250°C can reduce the generation of impurities such as Fe2O3 and Fe3O4, and then sintering is carried out at a higher temperature of 410-430°C at a slow heating rate of 1-5°C / min, which increases the pore diameter and volume of the particle surface and improves the degree of graphitization of the amorphous carbon coating. Finally, a sodium ferrous sulfate composite material with a porous surface and covered with a highly conductive carbon coating is obtained. The carbon coatings are interconnected to form a conductive network, which effectively improves the electrical conductivity of the material. At the same time, it effectively reduces the material's sensitivity to moisture and oxygen and improves its environmental stability.
[0025] Different from the method of combining high-energy mechanical ball milling technology and low-temperature solid-state sintering, the present invention omits the step of vacuum dehydrating FeSO4·7H2O to prepare FeSO4 which is required in the mechanical ball milling method, and can directly use FeSO4·7H2O aqueous solution as raw material. The operation steps are simple. The uniform amorphous carbon coating obtained by the method has a larger bonding area with the active particles, which is more conducive to constructing a highly conductive conductive network compared to the point contact between particles obtained by the ball milling method.
[0026] Different from the co-precipitation technology and the low-temperature solid-phase sintering technology, the present invention omits the use of a large amount of anhydrous ethanol and other hydrophobic alcohols as precipitation solutions, and uses vacuum rapid evaporation dehydration to replace the slow dropwise precipitation reaction and slow filtration in the co-precipitation technology, while avoiding the problem of recovery and reuse of a large amount of anhydrous ethanol. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the X-ray diffraction pattern (XRD) of the precursor material prepared in Example 1.
[0028] Figure 2 This is the X-ray diffraction pattern (XRD) of the sodium ferrous sulfate composite positive electrode material prepared in Example 1.
[0029] Figure 3 This is a scanning electron microscope image (SEM) of the sodium ferrous sulfate composite positive electrode material prepared in Example 1.
[0030] Figure 4This is the energy spectrum (EDS) of the sodium ferrous sulfate composite positive electrode material prepared in Example 1.
[0031] Figure 5 It is a constant current charge and discharge curve diagram of the sodium ion battery in Example 1.
[0032] Figure 6 1 is a cyclic voltammetry (CV) diagram of the sodium ion battery in Example 1.
[0033] Figure 7 This is the electrochemical impedance spectroscopy (EIS) of the sodium ion battery in Example 1.
[0034] Figure 8 This is a diagram of the first 20 charge and discharge cycles of the sodium ion battery in Example 1.
[0035] Fig. 9 This is the X-ray diffraction pattern (XRD) of the precursor material prepared in Example 2.
[0036] Fig.10 It is a constant current charge and discharge curve diagram of the sodium ion battery in Example 2.
[0037] Fig.11 This is the X-ray diffraction pattern (XRD) of the precursor material prepared in Comparative Example 1.
[0038] Fig.12 This is the X-ray diffraction pattern (XRD) of the precursor material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with specific embodiments.
[0040] Example 1
[0041] The synthesis steps of the sodium ferrous sulfate material used in the present invention are as follows: weigh 0.8875g of anhydrous sodium sulfate (Na2SO4), 1.7375g of ferrous sulfate heptahydrate (FeSO4·7H2O), and 0.11g of ascorbic acid, dissolve them in 10mL of deionized water, and stir them magnetically for 30 minutes to form a light green solution; the light green solution is quickly evaporated at 80°C in a vacuum to obtain a precursor powder.
[0042] After the precursor powder is evenly ground, it is quickly transferred to an alumina quartz boat, placed in a tubular furnace with an argon atmosphere, heated to 200°C at a heating rate of 5°C / min, and pre-fired for 2 hours. Then, the heating rate is adjusted to 1°C / min, and the temperature is raised to 425°C and calcined for 8 hours. After the calcination, an in-situ carbon-coated sodium ferrous sulfate positive electrode material is obtained.
[0043] Figure 1The X-ray diffraction pattern (XRD) of the precursor powder described in this example has a high degree of match with the standard card of Na2Fe(SO4)2·4H2O and good crystallinity. The diffraction peak (2theta=27.028°) shows the highest intensity, indicating that the (120) crystal plane is the dominant crystal plane.
[0044] Figure 2 The X-ray diffraction pattern (XRD) of the sodium ferrous sulfate composite positive electrode material described in this embodiment is similar to that of the Alluaudite type Na 2.5 Fe 1.75 The sample matched the standard card of (SO4)3 and had good crystallinity. No impurities Fe2O3 and Fe3O4 were observed. Meanwhile, the background of XRD diffraction pattern was high due to the generation of fluorescence signal caused by the detection of Fe-containing sample by Cu target.
[0045] Figure 3 This is a scanning electron microscope (SEM) image of the sodium ferrous sulfate positive electrode material. It can be clearly seen that the secondary particles are 5 to 10 μm in size and are aggregated from primary particles of 50 to 80 nm in size. The enlarged image shows that its surface has an obvious porous structure.
[0046] Figure 4 This is the energy spectrum (EDS) of the sodium ferrous sulfate positive electrode material. The spectrum shows that the main elements (Na, Fe, S, O) contained are evenly distributed.
[0047] The composite positive electrode material described in this embodiment is mixed with acetylene black (Super P) and polyvinylidene chloride (PVDF) in a mass ratio of 80:10:10, and 1-methyl-2-pyrrolidone is used as a dispersant. After the above materials are mixed evenly into a slurry, they are coated on an aluminum foil with a scraper. After vacuum drying at 120°C for 12 hours, a positive electrode sheet with a diameter of 11 mm is cut, a sodium metal sheet is used as a negative electrode, a glass fiber filter membrane (Whatman GF / D) is used as a diaphragm, and 1M NaClO4 is dissolved in EC:PC (volume ratio 1:1) and 5vol% FEC is added as an electrolyte. The stainless steel shell is used as the outer shell and assembled into a CR2032 button battery.
[0048] The sodium ion battery assembled by the above process has a voltage of 2.0 to 4.5 V (vs. Na / Na) at room temperature (25°C). + ) voltage range, the charge and discharge test was carried out, and the charge and discharge curve, cyclic voltammetry curve, electrochemical impedance spectrum and the charge and discharge curve of the first 20 cycles are shown in Figure 5 , Figure 6 , Figure 7 and Figure 8As shown. The median discharge voltage at 0.05C is about 3.6V, the reversible discharge specific capacity reaches 60mAh / g, and the battery discharge energy density is 216Wh / kg (based on the mass of the positive electrode active material). The cyclic voltammetry curve shows that there is an irreversible phenomenon in the first cycle of charge and discharge, which is caused by the irreversible migration of iron from the Fe1 site to the vacancy of the Na1 site during the first charge. It has two oxidation potentials near 3.25V and 3.75V, and three reduction potentials near 3.25V, 3.75V and 4.05V. At a rate of 0.1C, its discharge specific capacity reaches 55mAh / g, and after 20 cycles, it still maintains a specific capacity of 50mAh / g (1C=120mA / g), and the capacity retention rate reaches 90.9%.
[0049] Example 2
[0050] The synthesis steps of the sodium ferrous sulfate composite positive electrode material used in the present invention are as follows: weigh 0.8875g of anhydrous sodium sulfate (Na2SO4), 3.475g of ferrous sulfate heptahydrate (FeSO4·7H2O), and 0.11g of ascorbic acid, dissolve them in 10mL of deionized water, and stir them magnetically for 30 minutes to form a light green transparent solution; and quickly evaporate the light green solution at 100°C in a vacuum to obtain a precursor powder.
[0051] After the precursor powder is evenly ground, it is quickly transferred to an alumina quartz boat, placed in a tubular furnace with an argon atmosphere, heated to 200°C at a heating rate of 5°C / min, and pre-fired for 2 hours. Then, the heating rate is adjusted to 1°C / min, and the temperature is raised to 425°C and calcined for 8 hours. After the calcination, an in-situ carbon-coated sodium ferrous sulfate positive electrode material is obtained.
[0052] Fig. 9 This is the X-ray diffraction pattern (XRD) of the precursor powder described in this example, which completely matches the standard card of Na2Fe(SO4)2·4H2O (PDF#97-019-4363).
[0053] The sodium ferrous sulfate composite positive electrode material described in this embodiment is used to assemble the same sodium ion battery as in Example 1, and a charge and discharge test is performed at room temperature within a voltage range of 2.0 to 4.5 V. The charge and discharge curve is shown in FIG. Fig.10 The discharge median voltage at 0.05C is about 3.6V, and the first cycle discharge capacity is 40mAh / g (1C = 120mA / g).
[0054] Comparative Example 1
[0055] The synthesis steps of the sodium ferrous sulfate composite positive electrode precursor material used in the present invention are as follows: weigh 0.8875g of anhydrous sodium sulfate (Na2SO4), 3.475g of ferrous sulfate heptahydrate (FeSO4·7H2O), and 0.11g of ascorbic acid, dissolve in 10mL of deionized water, and stir magnetically for half an hour to form a light green transparent solution. The light green solution is rapidly evaporated at 110°C in vacuum to obtain a precursor powder.
[0056] Fig.11 The X-ray diffraction pattern (XRD) of the precursor powder in this comparative example completely matches the standard card of Na2Fe(SO4)2·2H2O (PDF#97-019-4362).
[0057] Comparative Example 2
[0058] The synthesis steps of the sodium ferrous sulfate composite positive electrode precursor material used in the present invention are as follows: 0.8875g of anhydrous sodium sulfate (Na2SO4), 1.7375g of ferrous sulfate heptahydrate (FeSO4·7H2O), and 0.11g of ascorbic acid are weighed, dissolved in 10mL of deionized water, and magnetically stirred for half an hour to form a light green solution. The light green solution is rapidly evaporated at 150°C in vacuum to obtain a precursor powder.
[0059] Fig.12 This is the X-ray diffraction pattern (XRD) of the precursor powder described in this comparative example. From the physical matching results, it can be seen that the precursor material Na2Fe(SO4)2·4H2O has been decomposed into impurities such as Na2Fe(SO4)2·H2O, NaSO4 and Fe(SO4)·H2O.
[0060] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material, characterized in that: The method steps include: (1) Na2SO4, FeSO4·7H2O and a water-soluble carbon source were added to deionized water and stirred thoroughly to obtain a uniform light green solution. The solution was then rapidly evaporated at 80°C under vacuum to obtain a precursor powder Na2Fe(SO4)2·4H2O. (2) Grinding the precursor powder Na2Fe(SO4)2·4H2O evenly, placing it in a tubular furnace under a protective gas atmosphere, first heating it to 200°C for pre-calcination for 1-2 hours, then heating it to 410-430°C for calcination for 8-12 hours, and obtaining an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material after the calcination; The amorphous carbon coating layer in the composite positive electrode material is tightly combined with the sodium ferrous sulfate particles to form uniform porous micron particles; The molar ratio of Na2SO4 and FeSO4·7H2O is 1:1, and the chemical formula of the in-situ carbon-coated sodium ferrous sulfate composite cathode material is Na 2.5 Fe 1.75 (SO4)3.
2. The method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: In step (1), the water-soluble carbon source is one or more of ascorbic acid, citric acid, hydroxymethyl cellulose and cyclodextrin.
3. The method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: The molar ratio of the water-soluble carbon source to FeSO4·7H2O is 1:10-100.
4. The method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: In step (2), the protective gas is an inert gas or a mixed gas of an inert gas and hydrogen; in the mixed gas, the volume fraction of hydrogen is 5% to 10%.
5. The method for preparing an in-situ carbon-coated sodium ferrous sulfate composite positive electrode material according to claim 1, characterized in that: In step (2), the heating rates during pre-calcination and calcination are 1-5°C / min, respectively.
6. An in-situ carbon-coated sodium ferrous sulfate composite positive electrode material, characterized in that: The composite positive electrode material is prepared by the method as described in any one of claims 1 to 5; the composite positive electrode material has a porous structure, a secondary particle size of 5 to 10 μm, and is formed by tightly stacked primary particles of 50 to 80 nm; amorphous carbon is coated on the surface of the primary particles, and the total mass of the amorphous carbon is 5 to 15 wt% of the total mass of the sodium ferrous sulfate composite positive electrode material.
7. A sodium ion battery, comprising a current collector, a positive electrode sheet, a negative electrode sheet, an electrolyte, a separator and a battery casing, characterized in that: The current collector is aluminum foil, the in-situ carbon-coated sodium ferrous sulfate composite positive electrode material described in claim 6 is the positive electrode, metallic sodium is the negative electrode, the glass fiber filter membrane is the diaphragm, and the electrolyte is a soluble sodium salt organic solution.
8. A sodium ion battery according to claim 7, characterized in that: The sodium ion battery positive electrode sheet is obtained by coating the slurry obtained by uniformly mixing the positive electrode, the conductive agent, the binder and the dispersant onto the aluminum foil current collector; the sodium ion battery negative electrode sheet is obtained by mechanically pressing metallic sodium and aluminum foil; the battery shell adopts a CR2032 battery shell.
9. A sodium ion battery according to claim 8, characterized in that: The conductive agent is one or more of acetylene black, Ketjen black and Super P; the binder is polyvinylidene chloride; the dispersant is 1-methyl-2-pyrrolidone; the soluble sodium salt in the electrolyte is sodium hexafluorophosphate or sodium perchlorate; the organic solvent in the electrolyte is one or more of ethylene carbonate, vinylene carbonate, propylene carbonate, dimethyl carbonate and fluoroethylene carbonate; the battery shell material is organic plastic, aluminum shell, aluminum-plastic film or stainless steel.
Citation Information
Patent Citations
Sodium ferrous sulfate / carbon nanotube composite positive electrode material, preparation method and sodium ion battery
CN115172724A